2019
DOI: 10.1021/acs.analchem.9b01699
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Taken by Dimeric Cu/Zn Superoxide Dismutase through the Protein Unfolding and Dissociation Landscape Is Modulated by Salt Bridge Formation

Abstract: Native mass spectrometry (MS) is a powerful means for studying macromolecular protein assemblies, including accessing activated states. However, much remains to be understood about what governs which regions of the protein (un)folding funnel are explored by activation of protein ions in vacuum. Here we examine the trajectory that dimeric Cu/Zn superoxide dismutase (SOD1) dimers take over the unfolding and dissociation free energy landscape in vacuum. We examined wild-type SOD1 and six disease-related point-mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
(157 reference statements)
1
9
0
Order By: Relevance
“…Hybrid MD–Monte Carlo approaches have been developed for the combined search of conformer and charge-isomer space in the gas phase. These indicate that side chains have a propensity to fold onto the protein surface with consequent structure contraction and formation of new hydrogen bonds and salt bridges, a prediction for which experimental evidence is emerging . Such structural rearrangements promote self-solvation and are compatible with maintenance of a native-like fold.…”
Section: Determining How Charges Are Distributed On the Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…Hybrid MD–Monte Carlo approaches have been developed for the combined search of conformer and charge-isomer space in the gas phase. These indicate that side chains have a propensity to fold onto the protein surface with consequent structure contraction and formation of new hydrogen bonds and salt bridges, a prediction for which experimental evidence is emerging . Such structural rearrangements promote self-solvation and are compatible with maintenance of a native-like fold.…”
Section: Determining How Charges Are Distributed On the Proteinmentioning
confidence: 98%
“…These indicate that side chains have a propensity to fold onto the protein surface with consequent structure contraction and formation of new hydrogen bonds and salt bridges, 70 a prediction for which experimental evidence is emerging. 73 Such structural rearrangements promote selfsolvation and are compatible with maintenance of a native-like fold. An interesting feature in the emerging picture of folded protein ions in the gas phase is their ability to compensate for the energetic penalty of charge separation in vacuo with favorable, conformation-specific intramolecular interactions, in line with growing experimental and theoretical evidence.…”
Section: Modelsmentioning
confidence: 99%
“…For example, a superoxide dismutase mutant containing an additional arginine exhibits altered stability in IM-MS due to the formation of an additional salt bridge after desolvation. 23 In solution, alkaline pH unfolds proteins by breaking salt bridges and H-bonds and causing coulombic repulsion due to the high density of negative charges. In positive ionization mode, the negative charges are neutralized mitigating their repulsive effect.…”
mentioning
confidence: 99%
“… The fact that proteins lacking basic residues favor the CRM over CEM reveals the limitations of using charge state signatures to assess the distribution of folded states . As a result, proteins with few ionizable groups may display diverging charging patterns upon unfolding. Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. ,,, Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures. Gas-phase unfolding is routinely used to identify compounds that can stabilize protein complexes by occupying specific binding pockets. , We find that moving charged sites can have a dramatic effect on a protein’s conformation in the gas phase.…”
Section: Discussionmentioning
confidence: 52%
“… Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. 9 , 15 , 54 , 55 Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures.…”
Section: Discussionmentioning
confidence: 74%